Riesgos físicos en los campos electromagnéticos, radiaciones no ionizantes y su incidencia en la población laboral del departamento de operaciones y mantenimiento de la empresa Guaguitel s.a. propuesta de un sistema de trabajo seguro. - Freire Ordoñez, Paúl Francisco (2015)
This work enables us to learn about the physical risks of electromagnetic fields of non-ionizing radiation on cell phone frequencies in the maintenance of a base radio, although to date the investigations are conducted not have conclusive scientific evidence to indicate that these affect humans, these same studies have determined the stocks exposure limits, which must be respected, work activities with non-ionizing radiation. In the present study we have performed measurements taking into account the main lobe of the issuer or antenna thereby I can determine that there are work activities necessary mind must be made with the equipment off radiation, in order to prevent possible damages, the personnel working in these activities, given that provision proposing a safe system of work which proposes a different process for performing maintenance on cellular base stations is performed.